An Analysis of Microbial Population of Chemostat Model in Fuzzy Environment (The Nepali Mathematical Sciences Report, 2019)
Chemostat is a continuous stirred tank reactor used for continuous microbial biomass production in commercial, medical and other research problems. While modeling real world phenomena through differential equations as backbone of practical problems, we need to introduce various parameters. These parameters may be vague, imprecise and uncertain. To incorporate these uncertainties, the notion of fuzzy differential equations is used in chemostat model as one of the tool. In this paper, we discuss some new results for the stability analysis of chemostat model and the results so obtained are justifiable analytically and verified graphically in fuzzy environment.